(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The ranking and accreditation systems have become popular method and being used as an acceptable tool for quality assessment of a Higher Education Institution(HEI). This paper attempts to study and examine the issues pertaining to Higher Education in India and whether Ranking and Accreditation systems have created qualitative environment in Indian HEIs or not. For this purpose, the response of academicians, academic administrators and senior managers of Indian HEIs have been sought through a Questionnaire method. Their responses have been examined with the help of various statistical tools and analysis of the same has been presented in this paper. This study highlights some important issues/challenges before Indian Higher Education which needs immediate attention. This study also reveals that the ranking and accreditation systems are having significant impact on the performance outcomes of Indian Higher Education Institutions. The outcome of the study has a relevance to stakeholders be it students, parents, educational administrators, academic fraternity, government, investors in higher education and society at large.